Optimalisasi Produktivitas dan Keselamatan Kerja Penambangan Menggunakan Metode Highdump Dumping Overburden - Muhammad Osaegi Restu Amrulloh; Ade Putro Setyo Wibowo; Endik Riyanto (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Coal mining activities involve three main activities, namely loading, hauling, and dumping. This research focuses on the technical study of overburden (OB) dumping highdump activities In Pit Dump area with the aim of planning, implementing and evaluating technical, operational, economic, and HSE aspects. This research method includes field observations, stage plan making, and high dumping over water. Actual conditions show a difference in critical dumping height over water with geotechnical recommendations to minimize landslide risk and potential hazards. The study involved the collaboration of Mine Engineer, Geotech Engineer, Safety, and Production, and the use of equipment such as Komatsu HD 785 and Komatsu Dozer D155 & D85. The results showed that these changes could be carried out productively and safely, supporting coal production targets and adding economic value to the government and Mining Business License holders.